Evaluation of implementation of patient involvement in Taiwan’s pharmaceutical reimbursement decision-making process - Tsai, Yi-Ling; Yang, Wen-Wen; Wu, Grace Hui-Min; Lin, Shih-Chang; Tang, Chao-Hsiun; Pwu, Raoh-Fang (International journal of technology assessment in health care, 2025)
Patient involvement enhances transparency, legitimacy, and responsiveness in pharmaceutical reimbursement decisions. Guided by the mosaic model, this study recognizes effective patient engagement requires diverse context-specific approaches. Despite Taiwan's National Health Insurance Administration (NHIA) implementing policies, gaps remain between intent and practice. This study evaluates NHIA's incorporation of patient inputs into reimbursement decisions and examines factors influencing involvement. We analyzed pharmaceutical company-initiated reimbursement submissions for catastrophic illnesses reviewed by the Pharmaceutical Benefit and Reimbursement Scheme Joint Committee (PBRS) from 2016 to 2023. Data sources included PBRS meeting records, the Online Patient Opinion Platform (OPOP), and NHIA notification E-mails. Generalized linear models identified predictors of patient involvement. The association between patient involvement and PBRS decisions was also explored. Patient involvement occurred in 28.4 percent (80/282) of all submissions, increasing from 17 percent (2016) to 44 percent (2023). Despite aligning with OPOP criteria, patient involvement remained incomplete. Discussion-type submissions, oncology drugs, and new drug applications showed higher involvement, whereas autoimmune diseases and new indication submissions had lower involvement. Budget impact and innovation categories were not significant predictors in adjusted models. The presence of patient involvement was not significantly associated with the PBRS approval rate. Ad hoc analysis revealed increased involvement for new indications following policy expansion. Despite NHIA's efforts, patient involvement implementation remains suboptimal. Structured mechanisms and expanded patient involvement beyond high-profile submissions and PBRS are crucial to broaden patient involvement. This study provides practical insights for East Asian healthcare systems advancing patient involvement amid limited empirical research.